The Effects of Heterogeneous Sanctions on Exporting Firms – Evidence from Denmark - Ina C. Jäkel; Søren Østervig; Erdal Yalcin (Center for Economic Studies and ifo Institute (CESifo), 2022)
Sanctions encompass a wide set of policy instruments restricting cross-border economic activities. In this paper, we study how different types of sanctions affect the export behaviour of firms to the targeted countries. We combine Danish register data, including information on firm-destination-specific exports, with information on sanctions imposed by Denmark from the Global Sanctions Database. Our data allow us to study firms' export behaviour in 62 sanctioned countries, amounting to a total of 453 country-years with sanctions over the period 2000-2015. Methodologically, we apply a two-stage estimation strategy to properly account for multilateral resistance terms. We find that, on average, sanctions lead to a significant reduction in firms' destination-specific exports and a significant increase in firms' probability to exit the destination. Next, we study heterogeneity in the effects of sanctions across (i) sanction types and sanction packages, (ii) the objectives of sanctions, and (iii) countries subject to sanctions. Results confirm that the effects of sanctions on firms' export behaviour vary considerably across these three dimensions.
Keywords: F51; F13; F14; F52; 330; sanctions; firm exports; trade margins